2015
DOI: 10.1016/j.neuroimage.2015.02.067
|View full text |Cite
|
Sign up to set email alerts
|

Network-level reorganisation of functional connectivity following arm amputation

Abstract: One of the most striking demonstrations of plasticity in the adult human brain follows peripheral injury, such as amputation. In the primary sensorimotor cortex, arm amputation results in massive local remapping of the missing hands' cortical territory. However, little is known about the consequences of sensorimotor deprivation on global brain organisation. Here, we used resting-state fMRI to identify large-scale reorganisation beyond the primary sensorimotor cortex in arm amputees, compared with two-handed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 55 publications
3
76
0
Order By: Relevance
“…However, Raffin et al78,79 reported that distinct and separate brain networks are activated by active or imagined movements, and these networks are similar between amputees and healthy controls. The preservation of the connections between cortex and periphery has been largely supported by Makin et al8083 in amputees. An integrative explanatory hypothesis for the mechanisms responsible for generating phantom pain suggests the potential of coexistence between reorganizational processes of the cortex with the expansion of cortical map neighboring the deafferented area and the abnormal spontaneous activity of the area now deprived of peripheral input 84.…”
Section: Discussionmentioning
confidence: 90%
“…However, Raffin et al78,79 reported that distinct and separate brain networks are activated by active or imagined movements, and these networks are similar between amputees and healthy controls. The preservation of the connections between cortex and periphery has been largely supported by Makin et al8083 in amputees. An integrative explanatory hypothesis for the mechanisms responsible for generating phantom pain suggests the potential of coexistence between reorganizational processes of the cortex with the expansion of cortical map neighboring the deafferented area and the abnormal spontaneous activity of the area now deprived of peripheral input 84.…”
Section: Discussionmentioning
confidence: 90%
“…This has been observed across neurologic disease, such as with the abnormal connectivity and distribution of dorsal attention and somatosensory networks in stroke patients 36 or the reorganized sensorimotor network in exhibited by amputees. 37 Studies based on ROIs in predefined locations are thus invariably subject to the criticism that the predefined location may not reflect an individual’s or disease-related reorganization of cortical function. To the extent that an analysis which utilizes a priori fixed ROI locations fails to capture such a reorganization, it would be comparably unable to capture a normalization (or move towards normalization) of connectivity after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the relative contribution of these two components of cortical reactivation, and their relation to functional recovery, remain less well understood, in large part because of the challenges and constraints imposed on longitudinal studies within individual animals by the invasive nature of electrophysiological mapping studies (Jain et al, 1997; Merzenich et al, 1983a; Merzenich et al, 1983b). Progress in high resolution functional MRI mapping now permits non-invasive longitudinal studies of cortical activation at high spatial resolution, with submillimeter coregistration of functional maps across sessions (Chen et al, 2012a; Corbetta et al, 2002; Frey et al, 2008; Lecoeur et al, 2011b; Lecoeur et al, 2011a; Makin et al, 2015a; Makin et al, 2015b; Moore et al, 2000; Yang et al, 2014; Zhang et al, 2010). Furthermore, by comparing cortical activation by low with high threshold pathways via low and high levels of tactile or electrocutaneous stimulation (ES), the relative contributions of dorsal and other pathways to local cortical innervation can be characterized (Dutta et al, 2014; Wang et al, 2012; Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%